Compression of noisy grayscale images with compression ratio analysis - Kryvenko, Sergii; Lukin, Vladimir; Bondzulic, Boban; Stojanovic, Nenad (Національний технічний університет "Харківський політехнічний інститут", 2025)
The object of the study is the process of compressing noisy images in a lossy manner by better portable graphics (BPG) encoder. The subject of the study is the method for adaptive selection of the coder parameter Q depending on noise intensity and image complexity. The goal of the study is to consider the basic characteristics of lossy compression of remote sensing images contaminated by additive white Gaussian noise with giving recommendations of preferable Q setting. Methods used: numerical simulation, verification for test images. Results obtained: 1) the dependencies of compression ratio on Q are monotonically increasing functions; 2) their characteristics are strongly dependent on noise intensity and image complexity; 3) dependencies of logarithm of CR on Q contain information on possible existence and position of optimal operation point for compressed noisy images; 4) compression ratios for large Q contain information on image complexity with low sensitivity to noise presence and intensity; 5) it is possible to get useful information from dependences of compression ratio on Q. Conclusions: the results of this research allow: 1) estimating image complexity; 2) adapting Q to noise intensity and image complexity.

Об'єктом дослідження є процес стиснення зашумлених зображень із втратами за допомогою покращеного портативного графічного кодера (BPG). Предметом дослідження є метод адаптивного вибору параметра Q кодера залежно від інтенсивності шуму та складності зображення. Метою дослідження є розгляд основних характеристик стиснення із втратами зображень дистанційного зондування, спотворених адитивним білим гаусовим шумом, з наданням рекомендацій щодо бажаного налаштування Q. Використані методи: чисельне моделювання, перевірка на тестових зображеннях. Отримані результати: 1) залежності ступеня стиснення від Q є монотонно зростаючими функціями; 2) їх характеристики сильно залежать від інтенсивності шуму та складності зображення; 3) залежності логарифма CR від Q містять інформацію про можливе існування та положення оптимальної робочої точки для стиснутих зашумлених зображень; 4) коефіцієнти стиснення для великих Q містять інформацію про складність зображення з низькою чутливістю до наявності та інтенсивності шуму; 5) можна отримати корисну інформацію із залежностей ступеня стиснення від Q. Висновки: результати цього дослідження дозволяють: 1) оцінити складність зображення; 2) адаптація Q до інтенсивності шуму та складності зображення.
Стиснення зображень в градаціях сірого з шумом з аналізом коефіцієнта стиснення
Keywords: lossy compression; better portable graphics; noise intensity; image complexity; стиснення з втратами; краща портативна графіка; інтенсивність шуму; складність зображення